Implementation of Character Education through Nationality Historical Learning in SMK Negeri Karangdadap Pekalongan Regency - Edy, Agus Nowo; Setyowati, Dewi Liesnoor; Wasino, Wasino (Universitas Negeri Semarang, 2018)
The government has issued a policy on cultural education and character of the nation as an effort to form the character of Indonesian human beings in harmony with the values ​​of national identity. The spirit of nationality is one of the character values ​​that will be embedded in the process of cultural education and character of the nation. The effort to internalize the character values ​​of the spirit of nationalism to learners is implemented through the learning process in school. This is the basis of research on the implementation of character education of national spirit through the learning of Indonesian history. The purpose of this study is to know the teacher's understanding of the character education policy, the ability to convey the values ​​of the spirit of nationalism in the practice of learning, knowing the supporting factors and constraints that occur in the implementation of character education. This research is qualitative descriptive and implemented in SMK Negeri Karangdadap Pekalongan Regency. Data collection techniques are done through observation, interviews, questionnaires and documentation. The results of the study show the teacher's ability to explain, interpret, sample, analyze and summarize the character values ​​of the spirit of nationalism, both listed in the character education policy and contained in historical learning materials. Based on these indicators it is concluded that teachers have an understanding of character education policy.